Using scales to clarify the transition from blue-phase to brown-phase fingerling in Notothenia rossii from the South Shetland Islands - Barrera Oro, Esteban; Alescio, Nadia Soledad; Moreira, María Eugenia; Marschoff, Enrique Ricardo (Polar Biology)
Scales and whole otoliths were read for age determination in early stages of Notothenia rossii caught in Potter Cove, South Shetland Islands, in summer seasons 2003-2006 and 2008. The sample comprised blue-phase pelagic fingerlings of 7.0-7.6 cm (TL) of age group 0 year and demersal brown-phase fingerlings/juveniles of 8.5-20.9 cm and predominant age groups 1-2 years. Counting of sclerites facilitated the interpretation of the rings, particularly in the central scale. To clarify two previous issues of controversy, we deduce that the duration of the offshore pelagic blue-phase fingerling stage is less than one year before migration to the nearshore demersal habitat. Furthermore, the first well-defined ring in scales corresponded to the first annulus, while a contiguous ring was a secondary ring sometimes deposited after the first winter during the second year of life, attributable to a shift of habitat from pelagic to demersal. A von Bertalanffy growth curve was computed by combining age/length data of the juvenile phase of N. rossii from this and a previous study at Potter Cove with literature data from the offshore adult population, resulting in the following equation: Lt = 86.9 (1-e-0.091(t-0.668)). Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Alescio, Nadia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Moreira, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Marschoff, Enrique Ricardo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del ...